SOCIAL INNOVATION PROJECT “BUSINESS SKILLS DEVELOPMENT AND BUSINESS OPPORTUNITIES AWARENESS PROGRAM FOR FAMILY WELFARE EDUCATION IN KAMPUNG KEDUNG KLINTER” - DAVINA CHRISTY; SHERLEEN GIANINA; AURELIA YOHANA; GIOVANI HOKINI (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This social innovation project unfolds as the